Giant Ectopic Minor Salivary Gland Tumour in Parapharyngeal Space - Nitish Baisakhiya; Shilpi Parihar; Ankit Mishra; Sweety Sen (Bengal Journal of Otolaryngology and Head Neck Surgery)
Introduction: Para pharyngeal tumours are rare head neck masses (0.5%). Most of them are benign. Deep location of this space and surrounding structures has led to emergence of many different approaches to this space reflecting the intrinsic difficulty in surgical access.